Imagining India : the idea of a renewed nation - Nilekani, Nandan (New York : Penguin Books, 2010)
India's recent economic boom has triggered tremendous social, political, and cultural change. The result is a country that, while managing incredible economic growth, has also begun to fully inhabit its role on the world political stage. In this far-ranging look at the central ideas that have shaped this young nation, Infosys cofounder Nilekani offers an original interpretation of the country's past, present, and future. He traces the efforts of the country's past and present leaders as they work to develop new frameworks that suit India's specific characteristics and challenges. He charts the ideas that are crucial to India's current infrastructure revolution and quest for universal literacy, urbanization, and unification; maps the ideological battlegrounds of caste, higher education, and labor reform; and argues that only a safety net of ideas--from social security to public health to the environment--can transcend political agendas and safeguard India's economic future.--From publisher description.
Includes bibliographical references (p. [471]-514) and index.
Keywords: India -- Economic policy; India -- Politics and government; India -- Civilization